1984
DOI: 10.1177/0013916584162005
|View full text |Cite
|
Sign up to set email alerts
|

Visual Preferences in Enclosed Urban Spaces

Abstract: Few design approaches have utilized scientific methods in dealing with aesthetic and visual factors. In an attempt to explore a scientific approach to environmental design, the relationship between visual preference and ratio variables in enclosed spaces on the Virginia Tech campus was investigated. Visual preference of enclosed spaces was measured by the Scenic Beauty Estimation (SBE) method. The SBE method was found to be reliable and valid in urban enclosed spaces. This study suggests that visual quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In particular, first and second-year students were classified as lower grade, and the rest were classified as upper grade. The variables “overseas travel experience” and “large city residence” are related to the familiarity of the environment being studied; the relationship between familiarity (and experience) and visual preference has also been examined in many studies [43,44,47]. For the variable “overseas travel experience,” the authors classified the participants’ travel experiences according to the period of travel in Western cities, because urban public squares enclosed by buildings are a more common type of public space in Western cities than in Oriental cities.…”
Section: Experiments Design and Analytical Frameworkmentioning
confidence: 99%
“…In particular, first and second-year students were classified as lower grade, and the rest were classified as upper grade. The variables “overseas travel experience” and “large city residence” are related to the familiarity of the environment being studied; the relationship between familiarity (and experience) and visual preference has also been examined in many studies [43,44,47]. For the variable “overseas travel experience,” the authors classified the participants’ travel experiences according to the period of travel in Western cities, because urban public squares enclosed by buildings are a more common type of public space in Western cities than in Oriental cities.…”
Section: Experiments Design and Analytical Frameworkmentioning
confidence: 99%
“…48)." Some other researchers examined the relationship between the D/H ratios and people's preference or perception of urban squares in quantitative ways [18][19][20]. Besides such discussions in the academia, this "ratio" theory has been broadly adopted in practice such as in design guidelines proposed by the public [21][22][23].…”
Section: D/h Ratio For Enclosurementioning
confidence: 99%
“…The quality of POSs can primarily be observed from the functional and the social perspective, whereby the two perspectives often overlap. Thus, the primary function of POSs involves providing space for every day or temporary use and the performance of necessary or optional leisure activities [46,50]. When residents spend their leisure time in the immediate surroundings of their home, it can help them identify with their residential surroundings and build stronger social relations [51,52].…”
Section: Public Open Spaces Within Inherited Large Housing Estates-sementioning
confidence: 99%
“…Green areas inside of POSs are key issues for LHE microclimate improvement [53]. Previous studies [50,[54][55][56][57] concluded that POSs should have a hierarchic order, while the spatial organization and urban equipment need to be properly implemented, in keeping with the POS function. The variety of content offered by the aforementioned activities can motivate the residents to use POSs for social interactions.…”
Section: Public Open Spaces Within Inherited Large Housing Estates-sementioning
confidence: 99%